2017
DOI: 10.21037/cdt.2017.05.03
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy study of routine echocardiography for bicuspid aortic valve: a retrospective study and meta-analysis

Abstract: Background: Transthoracic echocardiography (TTE) is the standard procedure to distinguish tricuspid aortic valve (TAV) from bicuspid aortic valve (BAV). Published studies assessed the accuracy of TTE for BAV under ideal conditions. Conversely, we aimed at assessing accuracy of TTE for BAV under routine conditions.Methods: This retrospective, cross-sectional study of 216 adults included 132 men aged 62±14 years.Of these, 108 had BAV and 108 were age-matched individuals with TAV. All diagnoses were confirmed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 84 publications
0
15
0
1
Order By: Relevance
“…Transthoracic echocardiography (TTE) is the most widely used cardiac imaging modality but is limited by intra-and interobserver variabilities. 28 Moreover, proximal aortic measurements by TTE may be less reliable than by CT or cardiac magnetic resonance, especially in the presence of asymmetric aortic root aneurysm. 29 Furthermore, echocardiography has a limited value in visualization of the more distal aorta (i.e., beyond the aortic root) and may therefore miss an aneurysm of the mid-ascending aorta.…”
Section: Aortic Stiffness/elasticity Parametersmentioning
confidence: 99%
“…Transthoracic echocardiography (TTE) is the most widely used cardiac imaging modality but is limited by intra-and interobserver variabilities. 28 Moreover, proximal aortic measurements by TTE may be less reliable than by CT or cardiac magnetic resonance, especially in the presence of asymmetric aortic root aneurysm. 29 Furthermore, echocardiography has a limited value in visualization of the more distal aorta (i.e., beyond the aortic root) and may therefore miss an aneurysm of the mid-ascending aorta.…”
Section: Aortic Stiffness/elasticity Parametersmentioning
confidence: 99%
“…non-tertiary care center, the presence of aortic aneurysm, and the presence of severe aortic valve calcification [5]. Although preoperative cardiac computerized tomography can be more accurate in differentiating between tricuspid and bicuspid aortic valves than TTE examinations, sufficient studies have not been implemented in the distinction between calcific/degenerative and post-inflammatory valves within the tricuspid aortic valves [25].…”
Section: Plos Onementioning
confidence: 99%
“…Thus, the evaluation and use of multimodality imaging, including transesophageal echocardiography, cardiac magnetic resonance imaging, and cardiac computed tomography, are highly recommended. Nevertheless, in selected cases such as congenital AS, there are still challenges in the preoperative identification of accurate AS etiology [5,6]. When these stenotic aortic valves meet the standardized criteria for severe status in symptomatic patients irrespective of their etiology, most patients are referred to cardiovascular surgeons for surgical or transcatheter aortic valve replacement (AVR).…”
Section: Introductionmentioning
confidence: 99%
“…However, the diagnostic accuracy of TTE is limited by operator dependency and possible impairment due to poor acoustic window, a large body habitus, limited field of vision, or technical artifacts. Recently, Hillebrand et al [ 9 ] demonstrated that concomitant aortic aneurysms and the presence of severe aortic valve calcifications resulted in an inaccurate diagnosis of BAV with TTE. In contrast, cardiac computed tomography (CCT) allows for detailed and accurate assessment of aortic valve morphology and ascending aorta dimensions in patients with BAV [ 10 11 ].…”
Section: Introductionmentioning
confidence: 99%